Magnetically recoverable TiO2-WO3 photocatalyst to oxidize bisphenol A from model wastewater under simulated solar light - Dominguez, S.; Huebra, M.; Han, C.; Campo Moreno, Pablo; Nadagouda, M. N.; Rivero, M. J.; Ortiz, I.; Dionysiou, D. D. (Springer, 2016)
A novel magnetically recoverable, visible light active TiO2-WO3 composite (Fe3O4@SiO2@TiO2-WO3) was prepared to enable the photocatalyst recovery after the degradation of bisphenol A (BPA) under simulated solar light. For comparison, the photocatalytic activity of other materials such as non-magnetic TiO2-WO3, Fe3O4@SiO2@TiO2, TiO2, and the commercial TiO2 P25 was also evaluated under the studied experimental conditions. The structure and morphology of the synthesized materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), and electron dispersion spectroscopy (EDS). Moreover, Brunauer-Emmett-Teller (BET) surface area and magnetic properties of the samples were determined. The Fe3O4@SiO2@TiO2-WO3 and TiO2-WO3 led to a BPA degradation of 17.50 and 27.92 %, respectively, after 2 h of the simulated solar light irradiation. Even though their activity was lower than that of P25, which degraded completely BPA after 1 h, our catalysts were magnetically separable for their further reuse in the treatment. Furthermore, the influence of the water matrix in the photocatalytic activity of the samples was studied in municipal wastewater. Finally, the identification of reaction intermediates was performed and a possible BPA degradation pathway was proposed to provide a better understanding of the degradation process.
Keywords: Bisphenol A (BPA); Degradation pathway; Magnetic composite; Photocatalysis; TiO2; WO3